Microscopic insights into the Faradaic reaction effects on the electric double layers. (6th April 2020) - Su, Haiping; Lian, Cheng; Gallegos, Alejandro; Deng, Shengwei; Shang, Yazhuo; Liu, Honglai; Wu, Jianzhong
Graphical abstract: Highlights: A simple molecular model for electric double layer (EDL) with Faradaic reactions is developed. The oxygen functional groups increase the Faradaic capacitance but have relatively little influence on the EDL capacitance. The theoretical predictions agree quantitatively with experimental observations. Abstract: Oxygen-containing functional groups have strong effect on the electrochemical capacitive behavior of carbon electrodes and have been subjected to many experimental investigations. However, there are relatively few theoretical reports on the relation between the oxygen-containing functional groups and the capacitance of carbon supercapacitors. In this study, we present a simple molecular model to describe electric double layer (EDL) in the presence of Faradaic reactions. We find that electrodes modified with oxygen functional groups increase the Faradaic capacitance but have relatively little influence on the EDL capacitance. The theoretical predictions agree quantitatively with experimental observations. We hope that this joint model by combining quantum DFT and classical DFT could provide a theoretical routine to study pseudocapacitors.